High-Throughput Gene Discovery in the Rat - Scheetz, Todd E.; Laffin, Jennifer J.; Berger, Brian; Holte, Sara; Baumes, Susan A.; Brown, Robert; Chang, Shereen; Coco, Justin; Conklin, Jim; Crouch, Keith; Donohue, Micca; Doonan, Greg; et al. (Genome Research, 2004)
The rat is an important animal model for human diseases and is widely used in physiology. In this article we present a new strategy for gene discovery based on the production of ESTs from serially subtracted and normalized cDNA libraries, and we describe its application for the development of a comprehensive nonredundant collection of rat ESTs. Our new strategy appears to yield substantially more EST clusters per ESTs sequenced than do previous approaches that did not use serial subtraction. However, multiple rounds of library subtraction resulted in high frequencies of otherwise rare internally primed cDNAs, defining the limits of this powerful approach. To date, we have generated >200,000 3′ ESTs from >100 cDNA libraries representing a wide range of tissues and developmental stages of the laboratory rat. Most importantly, we have contributed to ∼50,000 rat UniGene clusters. We have identified, arrayed, and derived 5′ ESTs from >30,000 unique rat cDNA clones. Complete information, including radiation hybrid mapping data, is also maintained locally at http://genome.uiowa.edu/clcg.html. All of the sequences described in this article have been submitted to the dbEST division of the NCBI.